Clinical isolates of Acinetobacter baumannii from a Portuguese hospital: PFGE characterization, antibiotic susceptibility and biofilm-forming ability. (April 2016) - Duarte, Andreia; Ferreira, Susana; Almeida, Sofia; Domingues, Fernanda C.
Highlights: PFGE analysis of the 79 A. baumannii isolates gave 9 different PFGE profiles. All A. baumannii isolates were resistant to 12 of the 17 tested antibiotics. 100% of the A. baumannii isolates were classified as MDR. 74.7% isolates showed ability to form biofilm. Isolates collected from the emergency unit showed higher ability to form biofilms. Abstract: Acinetobacter baumannii is an emerging pathogen associated with nosocomial infections that in addition has shown an increasing resistance to antibiotics. In this work the genetic diversity of A. baumannii isolates from a Portuguese hospital, their antibiotic resistance profiles and ability to form biofilms was studied. Seventy-nine clinical A. baumannii isolates were characterized by pulsed-field gel electrophoresis (PFGE) with 9 different PFGE profiles being obtained. Concerning the antimicrobial susceptibility, all A. baumannii isolates were resistant to 12 of the 17 tested antibiotics and classified as multidrug-resistant (MDR). In addition, 74.7% of the isolates showed biofilm formation ability, however no statistical significance with antibiotic resistance was observed. In contrast, urine samples isolates were more likely to form biofilms than strains isolated from other sources. Our findings highlight the high number of MDR A. baumannii isolates and the importance of the formation of biofilms as a potential virulence factor.